Use and acceptance of voice assistants among people with aphasia in Germany - Núñez Macías, Naizeth; Hielscher-Fastabend, Martina; Buschmeier, Hendrik (Frontiers in Communication, 2023)
Aphasia is an acquired disorder that affects the ability to communicate. The increasing availability of voice assistants (such as Amazon Alexa or Google Assistant) provides new opportunities to support people with aphasia in a variety of tasks, from everyday communication to speech and language therapy exercises. To ensure accessibility and acceptance, it is important to involve people with aphasia in the development process. Using the Unified Theory of Acceptance and Use of Technology (UTAUT2) as a theoretical framework, this study examines their willingness to use voice assistants and explores which potential applications they consider useful for participation in social and cultural contexts. These questions were addressed through a survey. Eight people with aphasia took part in the study. Although the sample size does not allow for statistical analysis, the results provide valuable insights for further research. Most of the participants showed a general interest in using voice assistants, two of them were already users. The presence of physical limitations motivates the use of speech-based technology. Participants who already used voice assistants saw them as a practical support in everyday life, while non-users had lower expectations in this respect. Social influence was found to play an important role. Participants' perceptions of privacy and data security issues varied and do not allow for generalization. Finally, some participants showed a preference for communication support applications (e.g., word finding, sentence formation, grammar support) over applications used for therapy exercises such as word training.